The impact of health literacy on smoking patterns among male residents: insights from Ningbo City - Tao, Zhenbo; Xu, Qianqian; Zhu, Yingying; Jin, Qiuyan; Chen, Lingwei; Ding, Shige; Zhao, Shuning; Dong, Ying (Frontiers in Public Health, 2025)
BackgroundThis study examined the associations between health literacy and smoking behaviors among residents in Ningbo City, Zhejiang Province, China, investigating both the impact of health literacy on smoking prevalence and intensity, and its potential role in smoking cessation interventions.MethodsThis cross-sectional study analyzed data from 2,948 male participants in the 2023 Health Literacy and Tobacco Use Surveillance Survey. We applied logistic regression models and restricted cubic spline analyses to assess the association between health literacy and smoking behaviors, adjusting for demographic characteristics, socioeconomic factors, and self-reported health status.ResultsOur findings indicate that higher levels of health literacy are associated with significantly lower rates of smoking (OR = 0.643, 95%CI = 0.528, 0.783) and daily cigarette consumption (β = −1.938, 95%CI = −3.649, −0.228). Non-smokers with higher health literacy were more likely to discourage others from smoking (OR = 1.464, 95%CI = 1.096, 1.955), underscoring health literacy’s crucial role in smoking prevention and control. A nonlinear relationship between health literacy and smoking behavior was identified.ConclusionHealth literacy significantly influences smoking behavior, with higher literacy levels associated with reduced smoking prevalence and intensity. These findings support incorporating health literacy enhancement into comprehensive smoking cessation strategies.